The 12-CK Score: Global Measurement of Tertiary Lymphoid Structures - Li, Roger; Berglund, Anders; Zemp, Logan; Dhillon, Jasreman; Putney, Ryan; Kim, Youngchul; Jain, Rohit K.; Grass, G. Daniel; Conejo-Garcia, José; Mulé, James J. (Frontiers in Immunology, 2021)
There is emerging evidence that the adaptive anti-tumor activity may be orchestrated by secondary lymphoid organ-like aggregates residing in the tumor microenvironment. Known as tertiary lymphoid structures, these lymphoid aggregates serve as key outposts for lymphocyte recruitment, priming and activation. They have been linked to favorable outcomes in many tumor types, and more recently, have been shown to be effective predictors of response to immune checkpoint blockade. We have previously described a 12-chemokine (12-CK) transcriptional score which recapitulates an overwhelming enrichment for immune-related and inflammation-related genes in colorectal carcinoma. Subsequently, the 12-CK score was found to prognosticate favorable survival in multiple tumors types including melanoma, breast cancer, and bladder cancer. In the current study, we summarize the discovery and validation of the 12-CK score in various tumor types, its relationship to TLSs found within the tumor microenvironment, and explore its potential role as both a prognostic and predictive marker in the treatment of various cancers.